Identification of MicroRNA–Potassium Channel Messenger RNA Interactions in the Brain of Rats With Post-traumatic Epilepsy - Li, Zheng; Ma, Yixun; Zhou, Fengjuan; Jia, Xiao; Zhan, Jingjing; Tan, Huachao; Wang, Xu; Yang, Tiantong; Liu, Quan (Frontiers in Molecular Neuroscience, 2021)
Background: Dysregulated expression of microRNAs and potassium channels have been reported for their contributions to seizure onset. However, the microRNA-potassium channel gene interactions in traumatic brain injury-induced post-traumatic epilepsy (PTE) remain unknown. Methods: PTE was induced in male rats by intracranial injection with FeCl2 (0.1mol／L, 1μL／min) at the right frontal cortex. Electroencephalography (EEG) was recorded at 60 min, as well as day 1, 7 and 30, and the behavioral seizures were assessed before injection and at different time points after injection. Rats were sacrificed on day 30 after injection. The right frontal cortex samples were collected and subjected to high throughput mRNA and microRNA sequencing. A network of differentially expressed potassium channel mRNAs and microRNAs was constructed using OryCun2.0 and subjected to GO and KEGG analyses. The differential mRNA and microRNA expressions were verified using qRT-PCR. The microRNA-mRNA was subject to Pearson correlation analysis. Results: A PTE rat model was successfully established, as evidenced by behavioral seizures and epileptiform discharges on EEG in PTE rats compared with sham rats. Among the 91 mRNAs and 40 microRNAs that were significantly differentially expressed in PTE rat brain, 4 mRNAs and 10 microRNAs were associated with potassium channels. Except for KCNN2, the other 3 potassium channel mRNAs were negatively correlated with 7 microRNAs. These microRNA-mRNA pairs were enriched in annotations and pathways related to neuronal ion channels and neuroinflammation. qRT-PCR and correlation analysis verified negative correlations in miR-449a-5p-KCNH2, miR-98-5p-KCNH2, miR-98-5p-KCNK15, miR-19b-3p-KCNK15, and miR-301a-3p-KCNK15 pairs. Conclusion: We identified microRNA-potassium channel mRNA interactions that are associated with PTE, providing potential diagnostic markers and therapeutic targets for PTE.